2017
DOI: 10.1002/mmce.21202
|View full text |Cite
|
Sign up to set email alerts
|

Design and analysis of wideband U-slot patch antenna with U-shaped parasitic elements

Abstract: A single layer single probe‐fed wideband microstrip antenna is presented and investigated. By cutting a U‐slot in the rectangular patch, and by incorporating two identical U‐shaped parasitic patches around both the radiating edges and the nonradiating edges of the rectangular patch, three resonant frequencies are excited to form the wideband performance. Details of the antenna design is presented. The measured and simulated results are in good agreement, the measured impedance bandwidth is 1.44 GHz (4.82‐6.26 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…The relative bandwidth of the antenna proposed in this paper reached 64.31% in the high-frequency band, which is far superior to that of the reference antennas [5,19,20]. This paper focuses on miniaturization [21] and high-frequency bandwidth [22] and the proposed antenna has great advantages in the above aspects. In the future, this antenna can be applied in the field of high-frequency broadband antennas.…”
Section: Resultsmentioning
confidence: 88%
“…The relative bandwidth of the antenna proposed in this paper reached 64.31% in the high-frequency band, which is far superior to that of the reference antennas [5,19,20]. This paper focuses on miniaturization [21] and high-frequency bandwidth [22] and the proposed antenna has great advantages in the above aspects. In the future, this antenna can be applied in the field of high-frequency broadband antennas.…”
Section: Resultsmentioning
confidence: 88%
“…The comparison of the proposed antenna with the recent implementations in various research works is shown in Table 2. It is observed that the proposed antenna is very compact in its size and provides more gain when compared with Refs.. [7][8][9][10][11][12][13][14] F I G U R E 1 4 Current distributions at 2.07 GHz The realized antenna model and its measurement using a vector network analyzer is shown in Figure 17.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, many geometries were proposed by researchers for the generation of multiband antennas. [6][7][8][9][10][11][12][13][14][15] All these models have less performance like narrow bandwidth, low gain and larger in size.…”
Section: Introductionmentioning
confidence: 99%
“…Techniques reported to enhance impedance bandwidth are to increase bandwidth by increasing planar area of the patch, by using shorting pins and creating defected ground . Some other techniques such as proximity coupling feed, aperture coupling feed and stack configuration are reported to enhance the bandwidth but these techniques may require multilayer structures thus increasing overall volume and cost of antenna …”
Section: Introductionmentioning
confidence: 99%
“…One of the standard techniques is to place parasitic patch/patches on the top of substrate and creating an electromagnetic coupling gap with radiating patch. It is used either in coplanar or stack geometries to enhance the impedance bandwidth and gain …”
Section: Introductionmentioning
confidence: 99%